2021
DOI: 10.1186/s12960-021-00609-9
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to online medical and nursing education during the COVID-19 pandemic: perspectives from international students from low- and middle-income countries and their teaching staff

Abstract: Background The COVID-19 pandemic posed a huge challenge to the education systems worldwide, forcing many countries to provisionally close educational institutions and deliver courses fully online. The aim of this study was to explore the quality of the online education in China for international medical and nursing students from low- and middle-income countries (LMICs) as well as the factors that influenced their satisfaction with online education during the COVID-19 pandemic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
0
33

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(199 citation statements)
references
References 31 publications
7
114
0
33
Order By: Relevance
“…One of the distinguishing characteristics of online learning is that students experience heightened autonomy in learning [9,32]. Li et al [14] reported that nursing students' learning attitude significantly affects their online learning outcomes. Therefore, self-regulation is considered a learner-centered construct that relates to how learners react to their situations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the distinguishing characteristics of online learning is that students experience heightened autonomy in learning [9,32]. Li et al [14] reported that nursing students' learning attitude significantly affects their online learning outcomes. Therefore, self-regulation is considered a learner-centered construct that relates to how learners react to their situations.…”
Section: Discussionmentioning
confidence: 99%
“…This has been a new but increasingly common experience for nursing students as colleges have begun employing online learning courses more actively in Korea [35]. Accordingly, online learning has become a promising and effective model for undergraduate nursing students [14].…”
Section: Implications For Nursingmentioning
confidence: 99%
See 1 more Smart Citation
“…Instructional design is of utmost importance. The expectation to lecturers to produce online learning material in a very short time without proper support and training negatively affected the academics during the pandemic (Li et al, 2021) and future situations should be avoided by equipped academics for online instructional design (Al-Nofaie, 2020). It must be student oriented, not only in terms of learning styles, and individualised learning, but must also consider the best way of assisting learners, within their realities.…”
Section: Higher Educationmentioning
confidence: 99%
“…As a consequence, the introduction of online system of education became a requisite to ensure the unhindered delivery of educational activities and this way, institutions were bound to reframe their curriculum accordingly. 6 This unexpected transition of educational system led to uncertainties among the nursing students. Many of the students expressed their concerns regarding the interruption of the programme following their removal from the clinical areas, which made them less confident and unsure about the progression of their course.…”
Section: Introductionmentioning
confidence: 99%